The Influence of Intrinsic Motivation and Compensation on Employee Performance: Study at one of the companies operating in the Fashion sector in Bandung City - Qulsum, Liza Novia; Kadir, Kadir (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
This study was undertaken to investigate the impact of intrinsic motivation and compensation on employee performance at a fashion company in Bandung City. This research investigates the elements that exert the greatest influence on employee performance in a fashion firm in the city of Bandung. Specifically, it focuses on the relationship between intrinsic motivation and compensation. The study involves 53 employees who will be surveyed using a questionnaire. Research utilizing route analysis indicates that the Intrinsic Motivation variable (X1) has a direct influence of 0.268 or 26.8%, an indirect influence through its link with Compensation (X2) of 0.163 or 16.3%, and a total influence of 0.431 or 43.1%. The Compensation Variable (X2) has a direct influence of 0.176 or 17.6%, an indirect influence through its relationship with Intrinsic Motivation (X1) of 0.163 or 16.3%, and a total influence of 0.339 or 33.9%. The coefficient of determination (R square) expresses the percentage that represents the magnitude of the contribution of the independent variables, Intrinsic Motivation and Compensation, which is 0.770 or 77%. The remaining 23% represents the influence of other factors on employee performance that were not studied, indicated by the value Ɛ = 0.230 or 23%. In relation to the research findings, it is recommended to focus on enhancing Employee Performance by addressing Intrinsic Motivation and Compensation.